(untitled) (Journal of Business and Technology (Dhaka), 2016)
The objective of this study is to examine the relationship between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP), bank size, the level of risk in the bank and Advertising Intensity (ADINT) in the Commercial Banks in Bangladesh. Sample selection has been made as per the purposive sampling process. The study is based on the secondary data and uses quantitative analysis approach. Data are collected from Review of CSR Initiatives in Banks brought out by the Central Bank of Bangladesh, annual reports of the respective banks and reputed Journals. The study period has covered from 1st July, 2012- 30th June, 2013. The study found that there is a significant relationship between levels of CSR and CFP, bank size, the level of risk in the bank and ADINT commercial banks in Bangladesh. Journal of Business and Technology (Dhaka) Vol.10(2) 2015; 57-66